Colombia : Economic Adjustment and the Poor - Liuksila, Claire (IMF Working Papers; Working Paper, 1991)
This paper assesses the impact on the poor of the macroeconomic adjustment program undertaken in 1985-86. It finds that program-induced changes in production, employment, and real incomes have benefited the poor, while the adverse impact of program-induced price changes was modest and was largely cushioned by government policies. The paper describes the dimensions of poverty in Colombia, surveys government programs to alleviate poverty, and reviews the factors contributing to the improvement in the income distribution in recent years.